2019
DOI: 10.32098/mltj.04.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Fatty infiltration of the shoulder: diagnosis and reversibility

Abstract: Fatty degeneration is a degenerative condition of the tendon-muscle unit of rotator cuff muscles, characterized by atrophy of muscle fibers, fibrosis, and fatty accumulation within and around the muscles. Many classification may be useful to stage this pathology, especially on Computed Tomography (CT) and magnetic resonance imaging (Mari) findings. Stem cell-based therapies for repair and regeneration of tendons and muscles may be used to promote healing and to make this condition reversible. Diagnosis and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…However, since it was not a main aspect of our study to evaluate the previously reported conventional MRI‐based predictors, we cannot rule out that we missed predictive effects due to our small cohort size and herefrom resulting low statistical power for the expected moderate‐to‐weak effects of these parameters. The tendon retear rate within our cohort was relatively high, yet still well in the range of previous reports …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, since it was not a main aspect of our study to evaluate the previously reported conventional MRI‐based predictors, we cannot rule out that we missed predictive effects due to our small cohort size and herefrom resulting low statistical power for the expected moderate‐to‐weak effects of these parameters. The tendon retear rate within our cohort was relatively high, yet still well in the range of previous reports …”
Section: Discussionsupporting
confidence: 89%
“…Patient stratification according to their individual SSP tendon/muscle properties currently relies on such MRI‐based morphological and patient‐related parameters. Whereas these without doubt support the treatment decision, their predictive value, especially for functional outcome remains controversially discussed . Accordingly, a relevant number of patients at risk for poor functional outcome or failed tendon healing remains undetected.…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical diagnosis, radiographic preoperative data and intraoperative parameters that can lead to positive or negative results or facilitate the incidence of complications, we selected three groups of patients, dedicating each one a specific level of care, as follows 2,6,9,12,[15][16][17][18][19][20][21][22][23][24][25] . Group A (low care, n=52): diagnosis of Primary OA, CTA, massive rotator cuff tear, absence of hyperkyphosis or scapular dyskinesia, Glenoid assessment according to Walch 16 A1 or A2 and according to Favard 17 E0, E1 and E2, Infraspinatus and Teres minor fatty infiltration according to Goutallier 18,22 less than 3, no spine nonunion, not repaired SSC, no intraoperative complications or tendon transfers. Group B (medium care, n=39): patients not included in Group A and C. Group C (high care, n=21): diagnosis of Arthroplasty Revision surgery, Fracture sequelae, Rheumatoid arthritis (grade 3 according to Levigne 19 ) or/and intraoperative complications or/and tendon transfers associated procedures.…”
Section: Patients Groups Featuresmentioning
confidence: 99%
“…Rotator cuff tears have also been associated with thyroid disease impacting metabolic functions of the tendon (5). Fat accumulation is a criterion frequently used as a prognostic factor to determine a patients' eligibility for surgical repair (2,4,6). Using magnetic resonance imaging (MRI), fat accumulation is scored on the Goutallier scale, a semi-quantitative assessment used to guide decisions for surgical intervention (3,4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Fat accumulation is a criterion frequently used as a prognostic factor to determine a patients' eligibility for surgical repair (2,4,6). Using magnetic resonance imaging (MRI), fat accumulation is scored on the Goutallier scale, a semi-quantitative assessment used to guide decisions for surgical intervention (3,4,6). Intramuscular fat accumulation in rotator cuff tears has been shown to have a strong association with a negative surgical outcomes (3).…”
Section: Introductionmentioning
confidence: 99%